PENGARUH UKURAN PERUSAHAAN, STRUKTUR MODAL, DAN LOAN TO DEPOSIT RATIO PADA KINERJA KEUANGAN - Shinta Meitasari, I Gusti Ayu; Budiasih, I Gusti AYu Nyoman (E-Jurnal Akuntansi, 2016)
This research aim was conducted with the purpose is to determine the effect of firm size, capital structure, and loan to deposit ratio (LDR) to the financial performance of LPD in Jembrana. The sample used in this study is as much as 56 LPD located in Jembrana that meet the criteria of purposive sampling. The analysis technique used in this research is multiple linear analysis. Results of the analysis concludes that the capital structure variables affect the financial performance LPD while variable size companies that proxied by the total variable employees and total assets variable has no effect on the financial performance of LPD. Likewise with variable loan to deposit ratio (LDR), which has no effect on the financial performance LPD in Jembrana.
Keywords: company size, capital structure, loan to deposit ratio (LDR), and financial performance